Website-Based Tourism Management Information System in Bahorok District Using Total Quality Management Method - Decfina, Fauziah; Raissa Amanda Putri (Jurnal Sistem Komputer dan Informatika (JSON), 2025)
This research aims to develop a website-based tourism management information system in Bahorok District as a solution to the problem of tourism data management that is still carried out manually and has not been digitally integrated. The approach used in this study is the Research and Development (R&D) method with the Rapid Application Development (RAD) system development model, as well as applying the principles of Total Quality Management (TQM) to ensure the quality of the system from the design stage to implementation. The RAD method allows system development to be carried out quickly and flexibly through an iterative process that directly involves users in refining the design and functionality of the system. The development stages start from needs analysis, quick design, prototype development, system testing, to implementation. The developed system includes key features such as Home Page, Tour Page, Information Page, About Page, as well as admin features for Manage Tour Data and Manage Reviews. The system test was carried out through functionality tests, usability tests, and security tests, with results showing that the system functions optimally, is easy to use, and is able to improve the efficiency of management and access to tourist information by the public. The implementation of TQM can be seen from the active involvement of users in the development process, validation of the system based on real needs, and a focus on continuous improvement of the quality of the system's display and services. The final results of the study show that the information system built successfully achieved the research goal, which is to provide an informative, interactive, and support effective tourism management and promotion. This research also contributes to the application of quality management in the development of public sector information systems and can be a reference for similar developments in other regions or sectors.